2007
DOI: 10.1128/iai.01143-06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Biofilm Formation-Defective Mutants of Staphylococcus aureus

Abstract: Staphylococcus aureus produces biofilm and this mode of colonization facilitates infections that are often difficult to treat and engender high morbidity and mortality. We have exploited bacteriophage Mu transposition methods to create an insertional mutant library in a highly biofilm-forming S. aureus clinical isolate. Our screen identified 38 insertions in 23 distinct genes together with one intergenic region that significantly reduced biofilm formation. Nineteen insertions were mapped in loci not previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 80 publications
8
112
4
Order By: Relevance
“…This was first noticed by Tu Quoc et al (2007) who observed a reduced capacity for producing biofilm in a cshA mutant of the S. aureus S30 strain, which is normally a strong biofilm producer. Moreover, cshA mutants exhibit stabilization of their agrBDCA mRNA, which is responsible for quorum sensing in S. aureus (Oun et al, in preparation).…”
Section: Phenotypic Readoutsmentioning
confidence: 79%
See 1 more Smart Citation
“…This was first noticed by Tu Quoc et al (2007) who observed a reduced capacity for producing biofilm in a cshA mutant of the S. aureus S30 strain, which is normally a strong biofilm producer. Moreover, cshA mutants exhibit stabilization of their agrBDCA mRNA, which is responsible for quorum sensing in S. aureus (Oun et al, in preparation).…”
Section: Phenotypic Readoutsmentioning
confidence: 79%
“…In Bacillus cereus, RNA helicases from the DEAD-box family were identified by mutagenesis to be required for survival at low temperatures, pH, and oxidative stress (Pandiani et al, 2010). Similarly, Tn916 mutagenesis identified an RNA helicase from the Gram-positive Clostridium perfringens to be involved in the adaptive response to oxidative stress (Briolat and Reysset, 2002), and random transposon mutagenesis identified a RNA helicase involved in the regulation of phenolic acid metabolism in Lactobacillus plantarum (Gury et al, 2004) and a RNA helicase (CshA) in S. aureus involved in biofilm formation (Tu Quoc et al, 2007). So far, however, their molecular function remains mostly elusive.…”
Section: Introductionmentioning
confidence: 99%
“…CodY is activated through direct interaction with the BCAAs as well as GTP (18 -20, 23) and, in its active state, represses transcription of upwards of 100 genes (17,24,25). Depletion of BCAAs and GTP results in derepression of CodY target genes, the products of which are involved in a range of cellular processes depending on the species, including sporulation (23), biofilm formation (26,27), protein degradation and utilization (22), and amino acid metabolism and transport (17,24). More recently, CodY has emerged as a regulator of virulence in S. aureus (28)(29)(30), implicating CodY as an important link between the nutrient status of the cell and virulence.…”
mentioning
confidence: 99%
“…6). In the S. aureus srrA transposon mutant, PIA synthesis was increased, whereas biofilm formation was decreased (23). This suggests that the mechanisms of biofilm formation regulated by SrrAB in S. epidermidis differ from those of S. aureus.…”
Section: Discussionmentioning
confidence: 66%
“…), suggesting a role in the retarded growth of S. aureus under anaerobic conditions (19). In addition, a transposon mutation in srrA resulted in reduction of biofilm formation in S. aureus, although PIA production was increased, suggesting that in S. aureus srrAB affects biofilm formation via an ica-independent pathway (23).…”
mentioning
confidence: 99%